Challenges in teaching and learning Arabic language in secondary school : students’, teachers’ and parents’ view - Norfaezah Mohd Hamidin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Issue of Arabic proficiency in Malaysia is never-ending and has always been the concern of policy makers and interested groups. This study aims to investigate students’, teachers’ and parent’s view towards challenges of teaching and learning Arabic at National Religious Secondary School (SMKA). The study employs a qualitatitave method. The participants of the study were three students, three teachers and three parents from three identified SMKAs at Selangor. A structured interview was used to gather the data for the study. The data were classified into several themes and analysed qualitatively. The study reveales that the challeges of teaching and learning Arabic depends on positive attitude towards the language itself. It was found that there was a lack of teaching method in teaching Arabic. The environment at the same time is not in favour of students to improve their Arabic language. Parents’ contribution in support teaching and learning in school was recommended.